Implementation of Village Apparatus Financial Accounting Applications: Challenges and Opportunities - Temalagi, Selva; Silooy, Marissa; Isnawati, Isnawati; Pattinaja, Elna M.; Haryadi, Dedi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
This article discusses the application of village apparatus financial accounting in terms of challenges and opportunities to improve the quality of work of village officials, especially in village financial management. To sharpen the discussion of the theme of this study, the authors have obtained some kinds of literature in the form of study findings that have been published in various accounting journals, both nationally and internationally. This study prioritizes secondary data in the form of study evidence that we examine in-depth involving data coding, data analysis, data interpretation, and concluding to obtain high validity and accountability answers. Based on the results of the data exposure and accompanied by an in-depth discussion, we finally found that there are still many villages apparatus that do not have HR tools that have the ability in financial governance, especially the use of technology applications for finance. This is the challenge that the application is straightforward easy to apply. However, village officials have their opposition, and they do not understand financial governance by integrating with accounting applications commonly used in various public financial management. Hopefully, these findings are helpful and give new hope in future studies.